A road map to generative safety culture: An integrated conceptual model - Ali, Shahid; Mohd Shaiful Zaidi, Mat Desa; Azizan, Ramli (IOP Publishing, 2019)
Evidence has shown that maturity models are a popular means of assessing safety culture in organizations. Maturity models involve defining maturity stages or levels from less to more advanced safety cultures. A maturity model is a descriptive model in the sense that it describes essential, or key, attributes that would be expected to characterize an organization at a particular level. Existing culture maturity models still lacks a concise roadmap of strategies that can guide an organization to progress through the maturity stages from less to advanced. This work proposes a concept to integrate the present general and workplace models and techniques that provides a roadmap to generative safety culture. In doing so, a summary of the current general and workplace literature will be provided, method to integrate them to develop an integrated conceptual model for a generative safety culture, as well as the final integrated model is discussed. This conceptual model can be the basis for further research in order to provide a comprehensive picture of the safety culture improvement and maturity process. Lastly, implications for specific interventions to develop targeted safety culture improvement practices and work towards achieving generative safety culture will be discussed.